Effect of different drying techniques on physical properties, total polyphenols and antioxidant capacity of blackcurrant pomace powders. (May 2017) - Michalska, Anna; Wojdyło, Aneta; Lech, Krzysztof; Łysiak, Grzegorz P.; Figiel, Adam
Abstract: The effect of freeze-drying (FD), convective (50 °C–90 °C; CD), microwave vacuum (120W, 240W, 360W, 480W; MVD) and combined (CD-MVD) drying on the physico-chemical properties of blackcurrant pomace powders was examined. A relationship was analysed between moisture content, water activity, solubility, true and bulk density, porosity, colour, total polyphenolic compounds, and antioxidant capacity and drying parameters. The lowest water activity was noted after CD suggesting that CD is more effective in water removal from pomace than MVD or CD-MVD. CD decreased solubility of powders to significantly greater degree than MVD and CD-MVD. Drying processes improved the colour of the blackcurrant pomace powders in comparison to the raw material. Power function between the temperature of the process and the changes in chroma was established, whereas a rational function was found during MVD. Functional relation between the temperature and total polyphenolic content and antioxidant capacity was found. Highlights: Drying methods affected physico-chemical properties of blackcurrant pomace powders. The final moisture content of CD samples was lower than that of MVD samples due to the experimental setting. Convective drying decreased solubility of blackcurrant pomace powders. Drying processes improved the colour of the blackcurrant pomace powders. A power function between process temperature and the chroma was established.